Utilizing Evidence-Centered Design to Develop Assessments: A High School Introductory Computer Science Course - Newton, Sunni; Alemdar, Meltem; Rutstein, Daisy; Edwards, Doug; Helms, Michael; Hernandez, Diley; Usselman, Marion (Frontiers in Education, 2021)
Evidence-centered design (ECD) is an assessment framework tailored to provide structure and rigor to the assessment development process, and also to generate evidence of assessment validity by tightly coupling assessment tasks with focal knowledge, skills, and abilities (FKSAs). This framework is particularly well-suited to FKSAs that are complex and multi-part (Mislevy & Haertel, 2006), as is the case with much of the focal content within the computer science (CS) domain. This paper presents an applied case of ECD used to guide assessment development in the context of a redesigned introductory CS curriculum. In order to measure student learning of CS skills and content taught through the curriculum, knowledge assessments were written and piloted. The use of ECD provided an organizational framework for assessment development efforts, offering assessment developers a clear set of steps with accompanying documentation and decision points, as well as providing robust validity evidence for the assessment. The description of an application of ECD for assessment development within the context of an introductory CS course illustrates its utility and effectiveness, and also provides a guide for researchers carrying out related work.